2020
DOI: 10.3390/s20082234
|View full text |Cite
|
Sign up to set email alerts
|

A Lightweight and Low-Power UAV-Borne Ground Penetrating Radar Design for Landmine Detection

Abstract: This paper presents the development of a lightweight and low-power Ground Penetrating Radar (GPR) to detect buried landmines in harsh terrain, using an Unmanned Aerial Vehicle (UAV). Despite the fact that GPR airborne systems have been already used for a while, there has yet been no focus on the UAV autonomy, which depends on the payload itself. Therefore, the contribution of this work is the introduction of a lightweight and low-power consumption GPR system, which is based on the Stepped Frequency Continuous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
57
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 24 publications
(23 reference statements)
0
57
0
Order By: Relevance
“…Concerning the last area of application, air-launched GPR systems based on Unmanned Aerial Vehicles (UAVs) have been developed in the last years [14][15][16][17][18]. Their main advantages are: (i) safety, as contact with the ground is avoided and thus the risk of accidental IED detonation is minimized; (ii) speed, as UAV-based systems are generally faster than autonomous terrestrial robots; and (iii) capability to inspect difficult-to-access areas.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning the last area of application, air-launched GPR systems based on Unmanned Aerial Vehicles (UAVs) have been developed in the last years [14][15][16][17][18]. Their main advantages are: (i) safety, as contact with the ground is avoided and thus the risk of accidental IED detonation is minimized; (ii) speed, as UAV-based systems are generally faster than autonomous terrestrial robots; and (iii) capability to inspect difficult-to-access areas.…”
Section: Introductionmentioning
confidence: 99%
“…Their main advantages are: (i) safety, as contact with the ground is avoided and thus the risk of accidental IED detonation is minimized; (ii) speed, as UAV-based systems are generally faster than autonomous terrestrial robots; and (iii) capability to inspect difficult-to-access areas. Analyzing the features of the different implemented prototypes [14][15][16][17][18], it can be concluded that the main challenges are the need for precise positioning and geo-referring of the GPR measurements, the limited UAV flight autonomy, and the choice of proper radiofrequency…”
Section: Introductionmentioning
confidence: 99%
“…The following Comment aims to correct some statements published in the article entitled "A lightweight and low-power UAV-borne ground-penetrating radar design for landmine detection" [1].…”
Section: Introductionmentioning
confidence: 99%
“…The radar has been tested with ground tests (Section 5.1 of [1]), as shown in Figure 12 of [1], where a B-scan was conducted. Then, in Section 5.2, authors show measurement results with the radar onboard a UAV, comparing the performance with other airborne-based Ground Penetrating Radar (GPR) systems in Section 5.3.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation